2021
DOI: 10.1134/s0026261721050118
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Assessment of Prokaryotic Diversity within Hypersaline Tuz Lake, Turkey

Abstract: Tuz Lake is the second biggest lake with an extreme hypersaline environment (over 32% (w/v) salt) in Turkey. It is reported that the lake was of marine origin, and its formation began with tensional movements during the Late Cretaceous and the Late Eocene. We conducted this research to determine the prokaryotic diversity of Tuz Lake by metagenomics approach, which is 16S rRNA amplicon sequencing of microbial communities in their natural environments. Hence, next-generation sequencing and then bioinformatic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It was also indicated that Ciliophora was one of the predators of bacteria and involved in symbiosis with algae (Chen et al, 2020). Moreover, the Bacteroidetes and Proteobacteria phylum, the most abundant bacterial phylum in Tuz Lake, showed the highest abundance in winter while decreasing in summer (Doğan & Kocabaş, 2021), similar to Ciliapore abundance. High temperature in summer and fall may adversely affect the distribution of Ciliapore in Tuz Lake as well as biological factors such as bacterial abundance (Table 1).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was also indicated that Ciliophora was one of the predators of bacteria and involved in symbiosis with algae (Chen et al, 2020). Moreover, the Bacteroidetes and Proteobacteria phylum, the most abundant bacterial phylum in Tuz Lake, showed the highest abundance in winter while decreasing in summer (Doğan & Kocabaş, 2021), similar to Ciliapore abundance. High temperature in summer and fall may adversely affect the distribution of Ciliapore in Tuz Lake as well as biological factors such as bacterial abundance (Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…The prokaryotic microbial diversity in Tuz Lake has been well described by 16S rDNA sequencing (Akpolat et al, 2021;Çınar & Mutlu, 2020;Doğan & Kocabaş, 2021;Oyewusi et al, 2021). However, the characterization and seasonal variation of the eukaryotic microbial community with environmental parameters in Tuz Lake is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinibacter spp. generally, requires light-driven pumps for growth and maintenance of ion gradients across the cell membrane (Dogan and Kocabaş, 2021). The low levels of genus Salinibacter in C1-3 may be attributed to relatively lower levels of solar radiation and lower temperatures (Kalwasinska et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hypersaline habitats are characterized as having a high salinity, high alkalinity, low oxygen concentration, and having halophilic microorganisms [2]. Halophilic cyanobacteria are known to be one of the major bacteria in high-salt concentration environments, such as hypersaline lakes, saline springs and soils, coastal hypersaline lagoons, and saltern evaporation ponds worldwide [2,3]. The halophilic cyanobacteria, a unicellular and filamentous species, form dense benthic mats in shallow solar salterns worldwide.…”
Section: Introductionmentioning
confidence: 99%